Makna Kata Hari (Yom) Dalam Ayub 3:1-10 - Bastanta Pradhana Bangun (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2022)
Abstract: This paper discusses the understanding and meaning of the day (yom) according to Job 3:1-10. The purpose of this research is to enrich the approach and interpretation of the interpretation of the Book of Job and open a new understanding which in the future is expected to have an impact on spiritual needs Christians are facing challenges in life that are increasingly difficult or complex, namely to see a new nuance of the relational relationship between humans and God. To achieve this, the main issues discussed in this paper are: how and to what extent does Job 3: 1-10 interpret the word "day"? The writing of this paper belongs to the scientific family of biblical theology and uses a grammatical-historical exegesis approach, while the data collection process is carried out through library research. The result of this study is that the meaning of the word yom contained in Job chapter 3 is interpreted from a pessimistic point of view which is an attempt by the wisdom teacher as an example of faith seeks understanding in exchanges between wise traditions and human experience.   Abstrak: Karya tulis ini membahas mengenai pemahaman dan makna hari (yom) menurut Ayub 3:1-10.Tujuan dari penelitian ini ialah untuk memperkaya pendekatan dan penafsiran tafsir akan Kitab Ayub dan membuka suatu pemahaman yang baru yang dikemudian hari diharapkan berdampak kepada kebutuhan rohani umat kristen dalam menghadapi tantangan hidup yang semakin sulit atau kompleks yakni untuk melihat sebuah nuansa baru akan hubungan relasional antara manusia dan Tuhan. Untuk mencapai hal ini, maka pokok permasalahan yang dibahas dalam karya tulis ini adalah: bagaimana dan sejauh manakah Ayub 3: 1-10 memaknai kata “hari” tersebut ?. Penulisan karya tulis ini termasuk dalam rumpun keilmuan teologi biblika dan mengunakan pendekatan eksegesis gramatikal-historis, sedangkan untuk proses pengumpulan data dilakukan melalui studi kepustakaan. Hasil dari penelitian ini ialah makna dari kata yom yang terdapat dalam Ayub pasal 3 dimaknai dari sudut pandang pesimis yang merupakan sebuah usaha sang guru hikmat sebagai sebuah contoh iman yang mencari pemahaman dalam pertukaran antara tradisi yang bijaksana dan pengalaman manusia.